Research Trends of Critical Thinking in Mathematics Problem Posing: A Bibliometric Study and Descriptive Content Analysis - Indri Rohmatul Fakhri Febriani; Pradnyo Wijayanti; Manuharawati; Endah Budi Rahaju (Universitas Negeri Surabaya, 2026)
This study aims to systematically review the development of research on critical thinking in problem posing through bibliometric analysis and descriptive content analysis of Scopus-indexed publications from 2015 to 2025. The results indicate that China, Indonesia, and the United States are the most influential countries in this field, with China occupying the leading position in both publications and citations. The most productive affiliation is the National Taiwan University of Science and Technology, and Hwang, G. emerges as the author with the greatest contribution. Publication trends show a sharp increase after 2020, reaching a peak in 2024 with seven published articles. Although critical thinking is strongly connected to problem posing, its relationship with creativity, problem solving, and critical pedagogy remains weak. Content analysis reveals a dominance of quantitative approaches, particularly quasi-experimental designs, with university students as the most frequently studied subjects, purposive sampling as the primary sampling method, and tests as the main measurement instruments. The most commonly used data analysis techniques include descriptive statistics, t-tests, ANOVA, and n-Gain. These findings highlight clear opportunities for further research, particularly in integrating critical pedagogy, creativity, and learning technologies, as well as in more deeply exploring the cognitive processes underlying critical thinking in problem posing.